Inclusion of Probiotics in Feeding Asian Seabass (Lates calcarifer) Fingerlings Improves Growth Performance, Body Composition, and Digestive Enzyme Activity - Priya, N. P.; Joseph, Shoji; Sibi, K. K.; Anjusoma, S. (Fishery Technology, 2025)
Asian Seabass (Lates calcarifer) fingerlings (4.21±0.68 g) were subjected to a 90-day feeding trial to evaluate the effects of various feeds and probiotic supplementation on growth performance, body composition, and digestive enzyme activities under controlled nursery conditions. The fish were fed three experimental diets: Feed CPFA and Feed CPFB, which are Commercial Pellet Feeds (CPF), and Feed C, which is a basal diet containing of trash/low-valued fish without probiotics. The other treatments included these basal diets supplemented with probiotics - SSP (Single-strain probiotics) and MSP (Multi-strain probiotics). Nine treatments, with three replicates, tested three diets, which included without probiotics, single-strain, and multi-strain probiotics. Fingerlings were stocked at 10 fish per 80-litre tank. The results indicated that growth parameters were significantly influenced (P